Alterations of the second stem of Lithuanian compound names as a resultof the interaction of Pagan and Christian name systems? - Sinkevičiūtė, Daiva (Baltistica, 2019)
In the Lithuanian Metrica one finds compound names whose second member coincides with Christian stems. The way these stems came about merits a special investigation, as it is a well established fact that the second stem is the most stable part of Lithuanian compound names. When new compound names are created, the second stem is usually taken from the old Lithuanian stock of compound names. The present research indicates that the second stems van-, vaš-, vant- and jont- arose through alteration of the stems vain-, vaiš- and jot-. The diphthongs of Lithuanian stems of the structure CVvC were written as monophthongs due to the influence of the Ruthenian language. Stems of the structure CVC were expanded by -t or -n- (after vowels) in order to bring them closer to the second stems of the structure CVCC. It thus seems that the coincidence of the second stem of some compound names with Christian names is a purely secondary phenomenon.